2017
DOI: 10.18632/oncotarget.17334
|View full text |Cite
|
Sign up to set email alerts
|

Dietary luteolin attenuates chronic liver injury induced by mercuric chloride via the Nrf2/NF-κB/P53 signaling pathway in rats

Abstract: Mercury exposure is a common cause of metal poisoning which is biotransformed to highly toxic metabolites thus eliciting biochemical alterations and oxidative stress. Luteolin, a phenolic compound found in many natural products, has multiple biological functions. Our study was aimed to explore the biological effects of luteolin in a liver injury model induced in rats by mercuric chloride (HgCl2). Criteria for injury included liver enzyme, glutathione and malondialdehyde levels, histopathology, TUNEL assay, hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 30 publications
6
35
0
Order By: Relevance
“…Pre-treatment with LUT significantly improved liver function biomarker levels and indicated that LUT could preserve hepatocyte integrity and relieve liver damage. This is consistent with the findings of Zhang et al [46] and Yang et al [22]. Tai et al [23] reported that LUT treatment improved the disturbance in levels of liver function markers evoked by acetaminophen and that was evident by regeneration of liver cells and healing of damaged hepatic parenchyma.…”
Section: Discussionsupporting
confidence: 91%
“…Pre-treatment with LUT significantly improved liver function biomarker levels and indicated that LUT could preserve hepatocyte integrity and relieve liver damage. This is consistent with the findings of Zhang et al [46] and Yang et al [22]. Tai et al [23] reported that LUT treatment improved the disturbance in levels of liver function markers evoked by acetaminophen and that was evident by regeneration of liver cells and healing of damaged hepatic parenchyma.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Luteolin increased the activity of SOD, CAT and the level of Nrf2 and its downstream targets HO‐1 and NQO1 in 3 % dextran sulfate sodium (DSS)‐treat rats . Besides, Luteolin increased the level of Nrf2 through Nrf2/NF‐ κ B/P53 signaling pathway in the presence of HgCl 2 which led to increased Bax and decreased Bcl‐2 . Furthermore, Luteolin inhibits HgCl 2 ‐induced renal injury by activating Nrf2 signaling pathway and increasing its subsequent protein HO‐1, NQO1 .…”
Section: Natural Polyphenols Nrf2 Activators In Multiple Disease Modelsmentioning
confidence: 99%
“…[56] Besides, Luteolin increased the level of Nrf2 through Nrf2/NF-κB/P53 signaling pathway in the presence of HgCl 2 which led to increased Bax and decreased Bcl-2. [57] Furthermore, Luteolin inhibits HgCl 2 -induced renal injury by activating Nrf2 signaling pathway and increasing its subsequent protein HO-1, NQO1. [58] Tangeretin (19) is a citrus polymethoxylated flavonoid that has been shown to have a wide range of pharmacological properties.…”
Section: Flavonementioning
confidence: 99%
“…Gadacha et al have reported that resveratrol acts as an antioxidant during the active phase and as a pro-oxidant during the inactive phase of rats [46], suggesting certain polyphenols have different effects depending on the intake timing. Several reports have revealed that high concentration of luteolin (80-100 mg/ kg) attenuates the liver injury and hepatotoxicity through the activation of Nrf2 [21,22]. Taken together, these results suggest that luteolin intake at the start of active phase may possess the powerful effect for prevention and amelioration to several diseases occurring from oxidative stress through the activation of Nrf2 even if the amount of luteolin is very low.…”
Section: Plos Onementioning
confidence: 67%
“…The serum concentration of luteolin reaches about 100 nM by dietary habit [19]. Luteolin possesses a lot of physiological functions including antioxidative activity [21,22], while the number of cultured cells and animal studies evaluate the effects in the concentration that exceeds the amount taken from the daily meal. On the other hand, our previous study revealed that the physiological nanomolarconcentration range of luteolin induces Nrf2/ARE pathway in human hepatoma HepG2 cells [23].…”
mentioning
confidence: 99%